Genetic potential of quality in spring bread wheat cultivars bred at Kurgan agricultural research institute - A. I. Abugalieva; L. T. Maltsevа; E. A. Filippova; A. I. Morgunov; Y. I. Zelensky; J. Peña (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. For the Trans-Urals, characterized by unstable climate over the years (alternating droughty and excessively moist years, recurrences of colds in spring, possibility of early frosts, etc.), grain quality is a prioritized genetic trait in spring bread wheat cultivars. In Kurgan Province, the share of thirdclass wheat varied since 1994 from 43% to 96%; only in the recent unfavorable years (2015 – 2017) it dropped to 11 – 27% due to rust epidemics. The aim of the study was to characterize the genetic potential of grain quality and its phenotypic implementation in promising cultivars bred at Kurgan Agricultural Research Institute and officially released for cultivation in the region.Materials and methods. The capacities of the KASIB4 – 13 (Kazakhstan–Siberia Wheat Improvement Network under the auspices of CIMMYT) represented by 17 breeding centers in Kazakhstan and Siberia were used to assess grain quality of 14 cultivars with different maturation time bred at Kurgan Agricultural Research Institute. Quality assessment was performed with due regard to the standards of Kazakhstan, CIS, and leading exporting countries, thus combining local and international levels, and employing genetic, biochemical and technological grain quality levels under different soil and climate conditions.Results and discussion. Generally, all cultivars demonstrated protein and gluten content and the level of vitreousness sufficient for strong and valuable wheat. The selected percentage was 92% for hard grain and medium hard grain wheat forms, up to 94% for high-protein and high-gluten ones, and up to 57% for genotypes without 1B/1R wheat/rye translocation. In terms of sedimentation, 86% of the genotypes were predicted to belong to the strong and valuable wheat class; according to the composition of HMW glutenin subunits, mixing quality and flour strength (W), 30 – 42% were identified as high-quality genotypes. The in-depth study of grain quality within the KASIB environmental network revealed heterogeneity among cultivars in a number of genetic and biochemical parameters and provided an opportunity to select high-quality genotypes by marker characteristics and technological properties, which is likely to improve the efficiency of intra-cultivar selection and overall quality assessment of cultivars.